Determinant of Early Marriage Adolescent to Risk Giving Birth Child in Case of Stunting - Widowati, Syafira Wahyu; Ira Nurmala; Devy, Shrimarti Rukmini; Aulia Dikmah Kiswahono (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Early marriage by adolescents aged less than 16 years can affect the reproductive health readiness of mothers or prospective mothers in giving birth to children with low birth weight potential and risk of stunting. Method: The method used for systematic article review was obtained from 5 databases with 15 relevant articles screened using the PRISMA method. Results: The results of the data obtained are that economic status is very influential on the incidence of stunting, this is due to poor fulfillment of toddler nutrition, lack of education of parents of toddlers, and lack of information and access to good health services. Conclusion: Educational background, economic status, cultural background and environment are the strongest factors that can encourage early marriage for adolescents with the majority living in less developed areas.